1995
DOI: 10.1016/0002-8703(95)90089-6
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum cardiomyopathy

Abstract: Congestive heart failure is an uncommon complication of pregnancy with potentially life-threatening consequences. Peripartum cardiomyopathy is a disease of unknown cause in which severe left ventricular dysfunction occurs during late pregnancy or the early puerperium. In the past, the diagnosis of this entity was made on clinical grounds; however, modern echocardiographic techniques have allowed more accurate diagnoses by excluding cases of diseases that mimic the clinical symptoms and signs of heart failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
226
1
29

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(260 citation statements)
references
References 62 publications
4
226
1
29
Order By: Relevance
“…Common misdiagnoses include other types of cardiomyopathy, valvulopathies, accelerated hypertension, diastolic ventricular dysfunction, systemic infection, pulmonary embolism, etc. 4 There is an increased incidence with multiple gestation, preeclampsia, obesity, advanced maternal age, 1 African descent and prolonged tocolysis. 4 Treatment includes digitalis, diuretics, vasodilators, and anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Common misdiagnoses include other types of cardiomyopathy, valvulopathies, accelerated hypertension, diastolic ventricular dysfunction, systemic infection, pulmonary embolism, etc. 4 There is an increased incidence with multiple gestation, preeclampsia, obesity, advanced maternal age, 1 African descent and prolonged tocolysis. 4 Treatment includes digitalis, diuretics, vasodilators, and anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…4 There is an increased incidence with multiple gestation, preeclampsia, obesity, advanced maternal age, 1 African descent and prolonged tocolysis. 4 Treatment includes digitalis, diuretics, vasodilators, and anticoagulants. 4 If supportive treatment fails, cardiac transplantation may be indicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it has been suggested that echocardiographicall), demonstrable impairment in left ventricular function should be added as a fourth criterion. 3 The obstetric, anesthetic and medical management of peripartum cardiomyopathy has been described previously, but dilated cardiomyopathy first presenting in early pregnancy is unusual. Although the clinical features of our patient resembled those ofperiparturn cardiomyopathy, the early presentation gave rise to a number of additional clinical considerations.…”
Section: Discussionmentioning
confidence: 99%